Molecular Docking of Anthraquinones from Morinda citrifolia Root as α-Glucosidase Inhibitors - Tobing, Aldi; Masriani, Masriani; Arief, Ihsanul (Universitas Pendidikan Mandalika, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and remains one of the major contributors to global morbidity and mortality. The development of safer and more effective antidiabetic agents from natural products has gained increasing attention due to the limitations of current synthetic drugs. Morinda citrifolia root has been reported to contain various anthraquinone derivatives with potential bioactivity. This study aimed to evaluate the inhibitory potential of 23 anthraquinone derivatives from Morinda citrifolia root against the α-glucosidase enzyme using an in silico molecular docking approach. Molecular docking was conducted using AutoDock Vina against α-glucosidase (PDB ID: 5ZCC) after protein preparation in UCSF Chimera. The docking targeted the catalytic site containing key residues (Arg411, Gln256, and Asp327) that interact with acarbose, and interaction patterns were analyzed using BIOVIA Discovery Studio Visualizer. The results demonstrated that several compounds exhibited stronger binding affinities than the standard inhibitor acarbose (-8.4 kcal/mol), while maintaining similar interaction patterns. In particular, compound 21 (-8.9 kcal/mol, H-bond with Gln256), compound 18 (-8.7 kcal/mol, H-bond with Arg411 and Gln256), and compound 15 (-8.3 kcal/mol, H-bond with Gln256 and Asp327) emerged as the most promising candidates. These findings suggest that anthraquinone derivatives from Morinda citrifolia root may serve as potential α-glucosidase inhibitors and warrant further pharmacokinetic and experimental validation.